The given equation is "(ye^{2xy}+x)dx+bxe^{2xy}dy=0" .
We know that a differential equation "Mdx+Ndy=0" is exact if
Therefore, according to question,
"M=(ye^{2xy}+x) \\ and \\ N=bxe^{2xy}"
Now,
"\\frac{\\partial (ye^{2xy}+x)}{\\partial y}=e^{2xy}+2xye^{2xy}=(1+2xy)e^{2xy}.......(1)"and
"\\frac{\\partial (bxe^{2xy})}{\\partial x}=be^{2xy}+2xybe^{2xy}=(1+2xy)be^{2xy}........(2)"from equation (1) and (2) ,we have the given differential equation is exact if "b=1" .
Now , putting b=1 in the given differential equation we get
"(ye^{2xy}+x)dx+xe^{2xy}dy=0"
"\\implies \\ ye^{2xy}dx+xdx+xe^{2xy}dy=0"
"\\implies \\ e^{2xy}(ydx+xdy)+xdx=0"
"\\implies \\ e^{2xy}d(xy)+xdx=0"
Integrating, we get
"\\frac{1}{2}e^{2xy}+\\frac{x^2}{2}=c"
where "c" is an integration constant.
Comments
Leave a comment